Two-phase coriolis mass flow metering with high viscosity oil. (March 2018) - Tombs, Michael; Zhou, Feibiao; Henry, Manus
Abstract: Previous work has described the use of Coriolis mass flow metering for multiphase flows, with applications in the oil and gas industry. This paper describes the development and testing of a Coriolis two-phase flow metering solution for nitrogen/synthetic oil mixtures with viscosities ranging from 50 cSt to 500 cSt, and with Gas Volume Fractions (GVFs) ranging from 0% to 90%. Formal trials took place at the UK National Flow Laboratory. A single synthetic oil was used; its viscosity was adjusted by controlling temperature. The results show that Coriolis metering is well suited to high viscosity oil/gas mixtures: in the formalized trials, mass flow errors for gas were mostly within 5% and for liquid were mostly within 2.5%. Achieving this accuracy up to 90% GVF represents an advance on previous work, which has been limited to around 50% GVF for low viscosity oils in two-phase and three-phase mixtures. Highlights: Two-phase (oil/gas) flow metering trials are described, using Coriolis Mass Flow metering. Formal trials have taken place at the UK National Flow Laboratory, TUV-NEL. The viscosity ranged from 50 cSt to 500 cSt and the gas volume fraction ranged from 0% to 90%. The liquid mass flow error was within ± 2.5%, and the gas mass flow error within ± 5.0%.